41P Pharmacotherapy preceding monocyte harvest interferes with the potency of monocyte-derived dendritic cell anticancer vaccine. (15th December 2019) - Hlavackova, E; Pilatova, K; Fedorova, L; Mudry, P; Mazanek, P; Sterba, J; Dubska, L Zdrazilova
Abstract: Background: Refractory and relapsing sarcoma and high-risk neuroblastoma show poor prognoses. Monocyte-derived dendritic cell anticancer vaccine could extend the treatment modalities in these patients. Pharmacotherapy prior to mononuclear cell harvest may influence the quality of manufactured dendritic cell product. Methods: In approved pediatric academic phase I/II clinical trial EudraCT 2014-003388-39 with primary safety endpoint an impact of preceding and concomitant therapy sixty days prior to mononuclear cell harvest on the manufactured anticancer vaccine quality characteristics in enrolled neuroblastoma and sarcoma subjects was statistically evaluated. The chemotherapeutic drugs, kinase inhibitors, biological therapeutics and growth factors were analysed. Results: Potency and quality control characteristic of thawed DCs included DC phenotype and 2-day cultivation DC phenotype, the production of IL-12 and IL-10 during 24-hour cultivation, allo-MLR and auto-MLR. Out of 47 enrolled subjects, pre-monocyte harvest treatment was evaluated in 23 (19 sarcoma, 4 neuroblastoma) subjects, of which 6 manufactured DC anticancer vaccines (5 sarcoma, 1 neuroblastoma) failed to pass quality control criteria. Dendritic cells from subjects pretreated with MTD-based dose of the alkylating agent (cyclophosphamide), topoisomerase I inhibitor (topotecan) and tyrosin kinase inhibitor (pazopanib) displayed impaired IL-12 production, depressed IL-12/IL-10 ratio, increased CD14 expression and poor T-cell stimulation in auto-MLR. Alkylating agent temozolomide (TMZ) together with topoisomerase I inhibitor (irinotecan) enabled the monocyte differentiation marked by decreased CD14 expression, however failed to display immunostimulatory properties with low CD80 expression and markedly decreased IL-12 production and IL-12/IL-10 ratio. Conclusion: Pharmacotherapy should be understood as concomitant factor influencing the DC vaccine product quality outcome. Certain monocyte-interfering anti-cancer pharmacotherapy combinations prior to monocyte harvest were associated with impaired quality and potency of DC-based immunotherapy. Clinical trial identification: EudraCT: 2014-003388-39. Legal entity responsible for the study: State Institute for Drug Control Czech Republic. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.